P083 CD1a expressing monocytes as sensors and mediators of inflammation in ulcerative colitis. (16th January 2018) - Al-amodi, O; Jodeleit, H; Beigel, F; Wolf, E; Siebeck, M; Gropp, R
Abstract: Background: CD1a presents self-lipids to the conventional CD4+ repertoire and thereby induces autoreactive T cells. CD1a expressing monocytes have been identified as biological markers of ulcerative colitis (UC). In this study the link between inflammatory and metabolic signals and CD1a expressing monocytes in vitro and in vivo was examined and CD1a was evaluated as a potential therapeutic target for treatment of UC. Methods: Peripheral blood mononuclear cells (PBMC) from UC patients and non-UC donors were incubated with phosphatidylcholine (PC) for 2 and 7 days and subjected to flow cytometric analysis. Proliferation was assessed by a cell trace assay. Triacylglycerol (TAG) and cholesterol levels and frequencies of CD14+CD1a+ monocytes were determined in a mouse model of UC which is based on NOD/scid IL2Rγnull mice reconstituted with peripheral blood mononuclear cells (PBMC) from UC patients (NSG-UC). NSG-UC mice were challenged with ethanol and treated with anti-CD1a antibodies. Response to treatment was determined by clinical- and histological scores, flow cytometric analysis of human leucocytes from spleen and colon and expression levels of TGFβ1, HGF, IFNγ and TARC. Results: Incubation of PBMC with PC resulted in a significant increase of frequencies of CD1a+ CD14+ monocytes at the expense of CCR2, CD86 and TSLPR expressing CD14+ monocytes. PC induced the activation and differentiation of Th cells. This effect was inhibited by anti CD1a antibody. In vivo, TAG ( p = 0.003) and cholesterol levels (0.003) increased upon inflammation and correlated positively with CD14+ CD1a+ monocytes (TAG: rho=0.5, p = 0.008; Cholesterol: rho=0.49, p = 0.007). Upon challenge NSG-UC mice developed symptoms and phenotype of colitis and frequencies of CD1a + monocytes were increased. Treatment with anti-CD1a antibodies resulted in a reduced clinical and histological score and in reduced frequencies of CD1a+ CD14+ monocytes in the colon and spleen of mice. Conclusions: CD1a expressing monocytes might act as sensors and mediators of inflammation in UC. Mice benefitted from treatment with anti-CD1a antibodies suggesting that CD1a might be a potential therapeutic target for UC.